Developing movement experiences with refugees to the United States who have undergone trauma. Issue 1 (2nd January 2021) - Dieterich-Hartwell, Rebekka; Haen, Craig; Kaimal, Girija; Koch, Sabine; Villanueva, Augusta; Goodill, Sherry
Abstract : Purpose: The purpose of this study is to investigate what resources recent refugees to the USA tap into and how collaborative expressive movements were experienced with regard to coping and resourcing, and to derive a theoretical model that would inform the use of dance/movement therapy and other holistic treatment modalities with refugees. Design/methodology/approach: A total of 13 refugees overall participated in parts of this study. Ten of these refugees completed movement sessions and semi-structured in-person interviews. Constructivist grounded theory methods and descriptive statistics were used to analyze the data. Findings: The findings suggest that refugees draw on a number of resources. The collaborative movement experiences seemed to have both a settling and mobilizing effect with the most important phenomenon of connection to the self or to another person. A grounded theory model, developed based on the findings, shows a dynamic interaction between the encountered categories. Research limitations/implications: The findings are preliminary and not transferrable because of limited size and potential researcher bias. Practical implications: The findings contribute to an understanding of the resettlement and acculturation phase of refugees with potential implications and suggestions for current clinical practices and health services. Originality/value: This study was original in its focus on understanding the role and the potential of body and expressive movement among refugees who have experienced trauma. Adherence to transformative paradigm principles invited participants to become co-researchers.